Bioactive Compounds and their Therapeutic Potential in Gastrointestinal Disease - Singh, Rudra Pratap; Soni, Shashank (Current Drug Research Reviews, 2025)
The gastrointestinal tract (GIT) is inhabited by an extensive range of microorganisms known as the human gut microbiota, which includes fungi, bacteria, viruses, algae, and parasites. Through its relationships with the host and other bacteria, this microbiota generates an intricate ecosystem that is essential to preserving human health. The gastrointestinal microbiota is necessary for many physiological functions, including immune system regulation, nutrition metabolism, vitamin synthesis, medication and xenobiotic processing, gut mucosal barrier integrity, and pathogen defense. An immune system's response to tissue damage or injury caused by infections, physical and chemical stress, immune system deviations, or genetic factors is inflammation. Chronic inflammation is a condition that is fueled by the activity of immune cells and has been linked with several diseases. While lifestyle adjustments, dietary alterations, and medicines are now used to reduce inflammation, these strategies frequently prove ineffective. Beyond the basics of nutrition, bioactive compounds (BCs), known as nutritional ingredients found in small quantities in foods and plant extracts, give additional benefits for health. Their anti-inflammatory, anticancer, anti-metabolic syndrome, antioxidant, and antimicrobial properties make them an excellent choice for addressing a variety of GIT disorders. By adjusting inflammatory mediators, bioactive compounds can lessen the negative effects of inflammation. Although medications, dietary changes, and changes in behavior are now employed to lower inflammation, these tactics usually fail to succeed. BCs, occasionally referred to as nutritious elements present in trace amounts in foods and plant extracts, provide additional health benefits beyond the essentials of nutrition. Bioactive substances may reduce the adverse effects of inflammation by modifying mediators of inflammation.
Keywords: bioactives